2006
DOI: 10.1016/j.biopsych.2005.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Oscillations in Offspring of Alcoholics: Neurocognitive Disinhibition as a Risk for Alcoholism

Abstract: Background-Event-related oscillations (EROs) are increasingly being used to assess neurocognitive functioning in normal and clinical populations. The current study compares different frequency activities in offspring of alcoholics (OA) and in normal controls (NC) in order to examine whether the OA group exhibits any abnormality in oscillatory activity while performing a Go/NoGo task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
101
1
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 108 publications
18
101
1
8
Order By: Relevance
“…The delta band differences reported in alcoholics (Kamarajan et al, 2004, Jones et al, in preparation) and offspring of alcoholics (Kamarajan et al, 2006) and in the present study closely corresponds to P300 differences reported in alcoholics and high risk subjects . It has been suggested that delta activity is generated by cortico-cortical interactions with some subcortical contributions.…”
Section: Event-related Delta Band Changessupporting
confidence: 90%
See 2 more Smart Citations
“…The delta band differences reported in alcoholics (Kamarajan et al, 2004, Jones et al, in preparation) and offspring of alcoholics (Kamarajan et al, 2006) and in the present study closely corresponds to P300 differences reported in alcoholics and high risk subjects . It has been suggested that delta activity is generated by cortico-cortical interactions with some subcortical contributions.…”
Section: Event-related Delta Band Changessupporting
confidence: 90%
“…Evoked theta power was not significantly different between the two groups, although few electrode locations in central and parietal regions showed weakly significant differences. Kamarajan et al (2006)in a study of oscillations in adult high risk offspring in a Go-Nogo P3 paradigm, also report a strongly reduced theta band power only in the parietal regions for the Go condition. The responses to the Go condition in this task closely resemble the oddball target condition, although the stimuli used in the task are different.…”
Section: Event-related Theta Band Changesmentioning
confidence: 88%
See 1 more Smart Citation
“…It is also supported by abnormalities in brain electrophysiology (e.g. Kamarajan et al 2006) and brain metabolism (e.g. Scheinsburg et al 2004) during the performance of response inhibition tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Disinhibition, i.e., the impaired ability to inhibit a potentially inappropriate response, is a common feature of substance misuse (Chen et al 2007; Kamarajan et al 2006;Kirisci et al 2006;Verdejo-Garcia et al 2006). Neuroimaging studies have reported both prefrontal and posterior parietal cortical involvement during inhibitory processing in healthy volunteers (Liu et al 2004), which may be overactive in populations with impulse control problems (Schulz et al 2004).…”
Section: Introductionmentioning
confidence: 99%